INTERNALISASI KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DAN IMPLIKASINYA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA : Studi Multisitus di SD Negeri Purwantoro I dan SD Negeri Blimbing III Malang - Indah Wahyuni; Heru Siswanto; Suparno (TA'LIM : Jurnal Studi Pendidikan Islam, 2026)
Professional competence is a competence that must be mastered by teachers in relation to the implementation of their main task of teaching. Meanwhile, in the National Education Standards, the explanation of article 28 paragraph 3 point c, it is stated that what is meant by professional competence is the ability to master learning materials broadly and deeply which allows guiding students to meet the competency standards set out in the National Education Standards. This study uses a qualitative approach, therefore the approach used is through a qualitative approach with a descriptive method. This approach is a process of systematic and intensive data collection to obtain knowledge about how the professionalism of Islamic Religious Education teachers and the professional competence of Islamic Religious Education teachers in forming the religious character of students at Purwantoro I Elementary School and Blimbing III Elementary School, Malang. The results of this study indicate that: (1) The professionalism of Islamic Religious Education teachers at Purwantoro 1 Elementary School and Blimbing III Elementary School, Malang, is based on having the ability (ability) and motivation (motivation), so that with this foundation Islamic Religious Education teachers are able to make plans, implement and supervise in forming the religious character of students; (2) The professional competence of Islamic Religious Education teachers in forming the religious character of students at Purwantoro I State Elementary School and Blimbing III State Elementary School, Malang, the form of religious character applied is Ilahiyah and Insaniyah. The findings of this study are the concept of professional competence of Islamic Religious Education teachers who have self-ability (self-ability to make plans, implementation, supervision to form students' religious character) and self-motivation (having self-motivation in increasing knowledge to form students' religious character).